REGENERASI IN VITRO TANAMAN TEBU (Saccharum officinarum L.): INDUKSI DAN PROLIFERASI KALUS, SERTA INDUKSI TUNAS - Ronald Bunga Mayang; Dwi Hapsoro; Yusnita Yusnita (Universitas Lampung, 2011)
This research is a series of activities that studies the embryogenesis for somatic clonal reproduction plant sugarcane multiplication in vitro which in-cludes the callus induction of explant pieces rolls up the leaves, the proliferation of embriogenic callus, and shoots induction of embriogenic callus. Those of three researchs were conducted in a series. This experiment were carried out in The Plant Science Laboratory, the Faculty of Agriculture, the University of Lampung, Indonesia, from Oktober 2010 until April 2011. All experiments were conducted in a completely random-ized design. Treatments of Experiment I were 2,4-D concentrations (0, 1, 2, and 3 mg/l) with and without 250 mg/l of casein hydrolysate, while those of Experiment II were combinations of those two chemicals, 2,4-D concentrations (1, 2, and 3 mg/l) with and without 250 mg/l of casein hydrolysate. Treatments of Experiment III were BA concentrations (1 mg/l and 2.5 mg/l). Results of the experiments showed that the best callus induction was achieved using MS media containing 3 mg/l 2,4-D, and callus induction was not significantly affected by casein hidrolysates. Concentrations of 2,4-D did not significantly influence em-bryogenic callus proliferation. The best shoot proliferation was attained in MS media containing 2.5 mg/l. Keywords: Benzyladenine (BA), 2,4-D, Casein Hydrolisate, sugarcane, and culture in vitro.